Normative or ethical approach to the problem of personal identity in contemporary Anglo-American philosophy - Olifer, Olena (Actual Problems of Mind, 2019)
The paper considers the problem of personal identity in normative or ethical approach, which developed in Anglo-American philosophy in 1990th. The article states that D. Parfit’s non-reductionism and E. Olson’s animalism contributed to its development. Normative approach treats person as moral agent, who constitutes own self in choices according to their own ideas of good. Personal identity is understood not as formal equality relation between two person-stages over time, but as constitution of self in the process of deliberation. The paper outlines the concept of practical identity by K. Korsgaard and the idea of personal identity as rational unity in agency-regarding relations by K. Rovane.